Strengthening energy security of Ukraine (Economics and region, 2024)
As part of the conducted research, the current situation in Ukraine regarding energy security was analyzed, revealing several critical factors that adversely affect the country's energy independence. These factors include dependence on imported energy resources, the presence of excessive transit capacities, and an insufficient level of energy efficiency in the national economy, as evidenced by the high energy intensity of GDP. The primary task in strengthening Ukraine's energy security amidst the challenges and threats posed by martial law is to ensure stable energy production and usage to support economic growth and improve the quality of life for the population. It is substantiated that to achieve energy independence, Ukraine must adopt a comprehensive approach that includes diversifying energy sources, modernizing infrastructure – particularly through the integration of digital technologies – decentralizing energy systems, enhancing energy efficiency, and actively collaborating with international partners. This will enable Ukraine to bolster its energy security and increase its level of energy independence.
Keywords: energy independence; energy efficiency; energy intensity; energy sector; critical energy infrastructure; decentralization of energy systems